2013
DOI: 10.1007/s11064-013-1044-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ROS-Activated p38MAPK Pathway is Involved in the Protective Effect of H2S Against Chemical Hypoxia-Induced Inflammation in PC12 Cells

Abstract: We have demonstrated the neuroprotection of hydrogen sulfide (H2S) against chemical hypoxia-induced injury by inhibiting p38MAPK pathway. The present study attempts to evaluate the effect of H2S on chemical hypoxia-induced inflammation responses and its mechanisms in PC12 cells. We found that treatment of PC12 cells with cobalt chloride (CoCl2, a hypoxia mimetic agent) enhanced IL-6 secretion, nitric oxide (NO) generation and expression levels of inducible nitric oxide synthase (iNOS) and neuronal nitric oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 31 publications
5
25
0
Order By: Relevance
“…More recently, we have demonstrated the cardioprotective effect of exogenous H 2 S against chemical hypoxia-induced insult by inhibiting oxidative stress and enhancing heat shock protein 90 (HSP90) expression [19,20]. Notably, the effects of H 2 S on the DOX-induced cardiotoxicity have attracted attention due to its antioxidant and anti-inflammatory effects [14,18,19,20,22,23,24]. The findings from in vivo and in vitro studies showed that DOX markedly reduces the endogenous H 2 S production in myocardium [25] or cardiomyocytes [7] and that exogenous H 2 S significantly improves the DOX-induced cardiac dysfunction [25] or cardiomyocyte injury [7] by its antioxidant effect.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, we have demonstrated the cardioprotective effect of exogenous H 2 S against chemical hypoxia-induced insult by inhibiting oxidative stress and enhancing heat shock protein 90 (HSP90) expression [19,20]. Notably, the effects of H 2 S on the DOX-induced cardiotoxicity have attracted attention due to its antioxidant and anti-inflammatory effects [14,18,19,20,22,23,24]. The findings from in vivo and in vitro studies showed that DOX markedly reduces the endogenous H 2 S production in myocardium [25] or cardiomyocytes [7] and that exogenous H 2 S significantly improves the DOX-induced cardiac dysfunction [25] or cardiomyocyte injury [7] by its antioxidant effect.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from in vivo and in vitro studies showed that DOX markedly reduces the endogenous H 2 S production in myocardium [25] or cardiomyocytes [7] and that exogenous H 2 S significantly improves the DOX-induced cardiac dysfunction [25] or cardiomyocyte injury [7] by its antioxidant effect. Furthermore, exogenous H 2 S attenuates the chemical hypoxia-induced inflammatory response in HaCaT cells [22] or PC12 cells [23] and ameliorates lipopolysaccharide (LPS)-triggered inflammation in microglia and astrocytes [24]. However, to our knowledge, no work has been focused on the protective effect of exogenous H 2 S against the DOX-induced inflammation and its mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of ROS may trigger multiple biological process, including apoptosis and programmed cell death (27). In a previous study on apoptosis caused by ultraviolet A (UVA) light, it was demonstrated that UVA triggers ROS-mediated apoptosis (27).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study on apoptosis caused by ultraviolet A (UVA) light, it was demonstrated that UVA triggers ROS-mediated apoptosis (27). In addition, the authors hypothesized that singlet oxygen is the dominant ROS.…”
Section: Discussionmentioning
confidence: 99%